ACTUAL PROBLEMS OF PEDAGOGY IN HIGHER EDUCATION (Journal of Science-Innovative Research in Uzbekistan, 2024)
The article is devoted to the problems of functioning and development of the modern system of higher education. This topic is relevant because the problems of the pedagogical process are complex and significantly affect the development of the country. The article reveals the prospects of overcoming the crisis phenomena in the field of education.